استخدام اساتذة التعليم الثانوي لمواقع التواصل الاجتماعي في العملية التعليمية - قرفي, سليمة; غرايسة, هاجر; العايب, يونس (جامعة الوادي - University of Eloued, 2023)
نهدف من خلال هذه الد ا رسة إلى الكشف عن مدى استخدام أساتذة التعليم الثانوي لمواقع التواصل الاجتماعي في العملية التعليمية ، من خلال د ا رسة عينة من اساتذة ثانويات ولاية الوادي وكذلك نهدف من خلالها التعرف على الاشباعات المحققة من هذا الاستخدام. بطرحنا للتساؤل الرئيسي التالي : ماهي استخدامات اساتذة التعليم الثانوي لمواقع التواصل الاجتماعي و الاشباعات المحققة منها؟ وقد اعتمدنا فيها على المنهج المسح من اجل الإجابة على التساؤل الرئيسي، ومعرفة كيف يستخدم أساتذة التعليم الثانوي لوسائل التواصل الاجتماعي في العملية التعليمية. كما اعتمدنا في ذلك على استمارة الاستبيان كأداة ، حيث كان حجم عينة الد ا رسة 40 من المبحوثين اخذت من 4 ثانويات من ولاية الوادي، التي تم اختيارها بطريقة عشوائية ، من أجل الإجابة على التساؤلات الفرعية التالية:  ما هي عادات وأنماط استخدام أساتذة التعليم الثانوي لمواقع التواصل الاجتماعي في العملية التعليمية؟  ماهي دوافع استخدام اساتذة التعليم الثانوي لمواقع التواصل الاجتماعي؟  ماهي الإشباعات المحققة من استخدام أساتذة التعليم الثانوي لمواقع التواصل الاجتماعي؟ وقد تم تقسيم الاستبيان إلى ثلاث محاور بالإضافة إلى صفات العينة، وقد توصلت الد ا رسة إلى جملة من النتائج أهمها:مواقع التواصل الاجتماعي المختلفة بنسبة 60 % - أغلبية المبحوثين يدفعهم الى استخدام مواقع التواصل الاجتماعي هو التواصل مع التلاميذ وهم بنسبة 42.5% - أغلبية المبحوثين يرون أن الأهداف التي يسعون الى تحقيقها من خلال استخدامهم لمواقع التواصل الاجتماعي هي الحصول على مختلف المعلومات بنسبة 45 % - أغلبية المبحوثين اشباع بدرجة متوسطة ما تحقق لهم مواقع التواصل الاجتماعي رغبات واشباعات معينة وهم 50 %ب الملخص بالإنجليزية Abstract Through this study, we aim to reveal the extent to which secondary education teachers use social networking sites in the educational process, by studying a sample of secondary teachers in El-Wadi state, as well as we aim to identify the gratifications achieved from this use. By asking the following main question: What are the uses of secondary ؟ education teachers for social networking sites and the gratifications achieved from them In it, we relied on the survey method in order to answer the main question, and to find out how secondary education teachers use social media in the educational processs We also relied on the questionnaire as a tool, as the sample size of the study was 40 respondents taken from 4 secondary schools in El-Wadi state, which were distributed randomly, in order to answer the following sub-questions What are the habits and patterns of secondary school teachers' use of communication sites ؟ social in the educational process What are the motives of secondary education teachers using social networking sites ؟ What are the gratifications achieved from the use of social networking sites by secondary school teachers ؟ The questionnaire was divided into three axes in addition to the characteristics of the sample The study reached a number of results, the most important of which are : The majority of the respondents use various social networking sites by 60% . The majority of respondents are motivated to use social networking sites by communicating with students, at a rate of 42.5% The majority of the respondents believe that the goals they seek to achieve through their use of social networking sites are obtaining various information by 45% . The majority of the respondents are moderately satisfied, as social networking sites achieve certain desires and satisfactions for them, and they are 50%
مذكرة ماستر إعلام وأتصال